LA INFLUENCIA DE LA PARTICIPACIÓN LABORAL DE LA MUJER EN EL DESARROLLO ECONÓMICO DE AMÉRICA LATINA Y EL CARIBE PERÍODO 1990-2016 - Torres Abrigo, María Paulina (2019)
There is a lot of discussion about the role that women should play within society, although the idea that is established in gender roles in which it is determined that a woman should perform as a housewife, limiting the possibilities of being part of the family, predominates. economic development of the countries. In the present research work entitled "The influence of labor participation of women in the economic development of Latin America and the Caribbean, period 1990-2016" whose general objective was to determine the relationship between women's participation in the workplace and the economic development in Latin America and the Caribbean, through an econometric model that allows to know the relevance of the inclusion of women in the economy, period 1990-2016. For the present investigation, data were taken both of the GDP per capita and of the labor participation rate of the World Bank's World Developed Indicators for 28 countries in Latin America and the Caribbean, during the years 1990 to 2016. The investigative techniques used were: bibliographic, statistical and econometric, for the analysis of the proposed model, the regression was generated under the generalized least squares modality, as well as a cointegration analysis with autoregressive vectors (VAR) and errore correction (VEC) for panel data, with which the following results were obtained: by means of the regression model of Generalized Least Squares (CGM), it was obtained that if the labor participation of women increases in 1% the GDP per capita of the countries of Latin America and the Caribbean increases by 0.89%. The variable GDP per capita and women's labor participation are of nature I (1), the same ones that are integrated in the long and short term, that is, they move together over time.